Effects of multiple cropping of farmland on the welfare level of farmers: Based on the perspective of poverty vulnerability - Peng, Jiquan; Chen, Lili; Yu, Bingwen; Zhang, Xiaohan; Huo, Zenghui (Frontiers in Ecology and Evolution, 2022)
This paper aims to explore the impact of multiple cropping on farmers’ welfare level and provide the theoretical and empirical basis for solving relative poverty in rural areas in the future. The paper uses data from the field survey of 1,120 farmers in Hubei in 2018 and uses the Endogenous Transformation Regression Model (ESR) and generalized propensity score matching (GPSM) model to construct a counterfactual framework. The paper analyses the effect of multiple cropping on farmers’ relative poverty and examines its mechanism. The result shows that: Multiple cropping of farmland can reduce the relative poverty of farmers through the mechanism of yield improvement path and factor intensification path. Under the counterfactual hypothesis, the relative poverty of farmers would increase by 28.43% if the farmers who participated in the multiple cropping did not; and that the relative poverty of the farmers would decrease by 29.57% if the farmers who did not participate in the multiple cropping participated. From the perspective of multiple cropping, the poverty reduction effect of multiple cropping in paddy fields is higher than that of dry land. From the perspective of the degree of multiple cropping, the poverty reduction effects of paddy fields and dryland will experience an increasing return to scale as the multiple cropping index increases. When the household equivalent scale adjustment coefficient is not used to eliminate the impact of family population structure on the “family per capita comparable income,” the artificially high results estimated by the model cannot truly reflect the poverty-reducing effect of multi-cropping of farmland. This paper argues that the government can guide farmers to choose the suitable mode of multiple cropping to reduce farmers’ vulnerability to relative poverty.